Technical constraints of integrating net energy metering from the Malaysian perspective - Celvakumaran P.; Ramachandaramurthy V.K.; Padmanaban S.; Padmanathan K.; Pouryekta A.; Pasupuleti J. (IEEE Computer Society, 2023)
Distributed power generation; Electric power distribution; Harmonic distortion; Power quality; Contribution to harmonic distortion; DIgSILENT PowerFactory; Net metering; Quality issues; Residential consumers; Solar photovoltaics; Solar PVs; Technical constraints; Solar power generation